Cell proliferative properties of Forcespinning® nopal composite nanofibers. (January 2022) - Rodriguez, Cristobal; Padilla, Victoria; Lozano, Karen; Ahmad, Fariha; Chapa, Alejandra; Villarreal, Alexa; McDonald, Andrew; Materon, Luis; Gilkerson, Robert
In this study, Forcespinning ® was used to produce nanofibers composed of Opuntia cochenillifera, "nopal, " mucilage (N) extract, chitosan (CH), and pullulan (PL) (N/CH/PL). These nopal-incorporating nanofibers were examined for their ability to sustain adhesion and proliferation of mouse embryonic fibroblast (NIH 3T3) cells. After a 6-day incubation period, N/CH/PL nanofibers displayed robust cell proliferation, with continued cell growth after an extended incubation period of 14 days. These results demonstrate that natural bioactive compounds can be combined with biodegradable polymers to provide an enhanced environment for cell growth, suggesting potential natural active ingredients as alternatives in wound dressings.